Strength training improves performance and pedaling characteristics in elite cyclists - Ronnestad, B. R.; Hansen, J.; Hollan, I.; Ellefsen, S. (Scandinavian Journal of Medicine & Science in Sports, 2015)
The purpose was to investigate the effect of 25 weeks heavy strength training in young elite cyclists. Nine cyclists performed endurance training and heavy strength training (ES) while seven cyclists performed endurance training only (E). ES, but not E, resulted in increases in isometric half squat performance, lean lower body mass, peak power output during Wingate test, peak aerobic power output (Wmax), power output at 4 mmol L-1 [la-], mean power output during 40-min all-out trial, and earlier occurrence of peak torque during the pedal stroke (P < 0.05). ES achieved superior improvements in Wmax and mean power output during 40-min all-out trial compared with E (P?<?0.05). The improvement in 40-min all-out performance was associated with the change toward achieving peak torque earlier in the pedal stroke (r = 0.66, P < 0.01). Neither of the groups displayed alterations in VO2max or cycling economy. In conclusion, heavy strength training leads to improved cycling performance in elite cyclists as evidenced by a superior effect size of ES training vs E training on relative improvements in power output at 4 mmol L-1 [la-], peak power output during 30-s Wingate test, Wmax, and mean power output during 40-min all-out trial.